Effect of Relative Humidity on the Tribological Properties of Self-Lubricating H3BO3 Films Formed on the Surface of Steel Suitable for Biomedical Applications. (26th August 2015) - Hernández-Sanchez, E.; Chino-Ulloa, A.; Velazquez, J. C.; Herrera-Hernández, H.; Velázquez-Mancilla, R.; Carrera-Espinoza, R.
Abstract : The effect of environmental humidity on the self-lubricating properties of a thin film of boric acid (H3 BO3 ) was evaluated. H3 BO4 films were successfully formed on the surface of AISI 316L steel. The study was conducted on AISI 316L steel because of its use in biomedical applications. First, the samples were exposed to boriding to generate a continuous surface layer of iron borides. The samples were then exposed to a short annealing process (SAP) at 1023 K for 5 min and cooled to room temperature while controlling the relative humidity (RH). Five different RH conditions were tested. The purpose of SAP was to promote the formation of a surface film of boric acid from the boron atoms present in the iron boride layers. The presence of the boric acid at the surface of the borided layer was confirmed by Raman spectroscopy and X-ray diffraction (XRD). The self-lubricating capability of the films was demonstrated using the pin-on-disk technique. The influence of RH was reflected by the friction coefficient (FC), as the samples cooled with 20% of RH exhibited FC values of 0.16, whereas the samples cooled at 60% RH showed FC values of 0.02.